Banker and customer relationship and the accounts of personal customers - Mather, L. C. (London : Waterlow, 1966)
Explanations on the duties and responsibilities of bankers to their customers and the duties of the customers to the bankers.
Includes index.
sju 24/01/2019
Loans
Keywords: Banking law